Low temperature diamond growth arising from ultrafast pulsed-laser pretreatment. (May 2018) - Krzyżanowska, Halina; Paxton, William F.; Yilmaz, Mesut; Mayo, Anthony; Kozub, John; Howell, Mick; Gregory, Justin; Butler, James E.; Kang, Weng Poo; Mu, Richard; Davidson, Jimmy L.; Tolk, Norman H.
Abstract: At temperatures significantly lower than normal growth temperatures using the hot filament chemical vapor diamond deposition approach, we have observed growth of high quality diamond films resulting from the application of in situ ultrafast pulsed-laser irradiation as a pretreatment step, on a conventionally abraided Si substrate surface. Low-temperature growth is seen to occur only where the sample was pretreated by laser irradiation. This effect is correlated with the formation, above a particular laser fluence threshold, of laser induced periodic nanostructures on the silicon substrate surface, with characteristic lengths significantly less than the laser wavelength, λ. The origin of these previously observed features will be discussed. Diamond growth samples were characterized using scanning electron microscopy and micro-Raman spectroscopy. This work strongly indicates that appropriate ultrafast-laser pretreatment shows promise as a means of promoting high-quality low-temperature CVD diamond growth in predetermined patterns, thus, demonstrating potential as a technique for the fabrication of diamond-based devices and selective diamond growth on semiconductor substrates. Graphical abstract: Image 1